Chemical Composition, Nutritive Value, and Toxicological Evaluation of Bauhinia cheilantha Seeds: A Legume from Semiarid Regions Widely Used in Folk Medicine. (17th April 2013) - Teixeira, Daniel Câmara; Farias, Davi Felipe; Carvalho, Ana Fontenele Urano; Arantes, Mariana Reis; Oliveira, José Tadeu Abreu; Sousa, Daniele Oliveira Bezerra; Pereira, Mirella Leite; Oliveira, Hermogenes David; Andrade-Neto, Manoel; Vasconcelos, Ilka Maria
Abstract : Among the Bauhinia species, B. cheilantha stands out for its seed protein content. However, there is no record of its nutritional value, being used in a nonsustainable way in the folk medicine and for large-scale extraction of timber. The aim of this study was to investigate the food potential of B. cheilantha seeds with emphasis on its protein quality to provide support for flora conservation and use as raw material or as prototype for the development of bioproducts with high added socioeconomic value. B. cheilantha seeds show high protein content (35.9%), reasonable essential amino acids profile, low levels of antinutritional compounds, and nutritional parameters comparable to those of legumes widely used such as soybean and cowpea. The heat treatment of the seeds as well as the protein extraction process (to obtain the protein concentrate) increased the acceptance of diets by about 100% when compared to that of raw Bc diet. These wild legume seeds can be promising alternative source of food to overcome the malnutrition problem faced by low income people adding socioeconomic value to the species.